Characterization of Road Traffic Emissions in a Densely Populated Residential Area of Kuwait - Jallad, Karim (2012)
Analysis of road traffic emissions in the Salmiyah residential area of Kuwait was conducted over a period of 12 months, from March 2008 to February 2009. Salmiyah is a densely populated area, mainly by expatriates. Apartment buildings are the dominant type of dwellings available in Salmiyah. Major highways surround this residential area where heavy traffic congestion occurs during rush hours. The objectives of this work were: to monitor ambient tropospheric levels of carbon monoxide (CO), nitrogen dioxide (NO2), sulfur dioxide (SO2), non-methane hydrocarbons (NMHC), and ozone (O3), to understand their diurnal behaviors, and to study their seasonal trends. The results of this study indicated that (i) CO, NO2, SO2, NMHC and O3 exceeded the ambient air quality standards during specific times of the year; (ii) the diurnal patterns for CO, SO2, NO2, and NMHC showed three peaks which were directly dependent on high traffic density, while only two daily maxima were observed in the case of O3; (iii) O3 compared to the other gaseous pollutants exhibited a completely opposite monthly mean distribution since the highest concentration levels were detected during the summer season (July and August).